2015
DOI: 10.1111/cei.12657
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide inhibits T cell activation in target organs during systemic lupus erythematosus

Abstract: SummarySystemic lupus erythematosus is characterized by the presence of circulating anti-nuclear antibodies (ANA) and systemic damage that includes nephritis, haematological manifestations and pulmonary compromise, among others. Although major progress has been made in elucidating the molecular mechanisms responsible for autoimmunity, current therapies for lupus have not improved considerably. Because the exposure of carbon monoxide (CO) has been shown to display beneficial immunoregulatory properties in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
(85 reference statements)
2
25
0
Order By: Relevance
“…CO is another metabolite of HO-1, which has been demonstrated to exert anti-inflammatory, antiapoptotic and cytoprotective effects in several types of diseases (Otterbein, 2002;Chung et al, 2008). CO has been reported to inhibit the expression of proinflammatory molecules on the cell surface (Riquelme et al, 2015a), regulation of mitochondrial function (Riquelme et al, 2015b) and inhibit T cell activation (Mackern-Oberti et al, 2015). With relevance to the present study, previous findings have reported an association between CO and viral replication in host cells.…”
Section: Introductionsupporting
confidence: 59%
“…CO is another metabolite of HO-1, which has been demonstrated to exert anti-inflammatory, antiapoptotic and cytoprotective effects in several types of diseases (Otterbein, 2002;Chung et al, 2008). CO has been reported to inhibit the expression of proinflammatory molecules on the cell surface (Riquelme et al, 2015a), regulation of mitochondrial function (Riquelme et al, 2015b) and inhibit T cell activation (Mackern-Oberti et al, 2015). With relevance to the present study, previous findings have reported an association between CO and viral replication in host cells.…”
Section: Introductionsupporting
confidence: 59%
“…Carbon monoxide (CO) as a component of the gas phase of cigarette smoke is associated with anti-inflammatory properties. CO reduces antigen presentation by APCs and prevents the maturation of dendritic cells (DCs) (Sheikh et al 2011, Riquelme et al 2016, Mackern-Oberti et al 2015. CO-treated DCs retained the capacity to secrete anti-inflammatory cytokine IL-10 despite losing their ability to produce pro-inflammatory cytokine IL-12 (Riquelme et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the HO‐1 expression is down‐regulated in monocytes isolated from patients with SLE and HO‐1 induction has been associated with disease amelioration in murine lupus . Finally, carbon monoxide, which is a product of HO‐1 enzymatic activity over heme group, decreases activated T‐cell numbers in kidneys and lungs, and decreases levels of anti‐nuclear antibodies (ANA) in lupus‐prone mice …”
Section: Introductionmentioning
confidence: 99%
“…21 Finally, carbon monoxide, which is a product of HO-1 enzymatic activity over heme group, decreases activated T-cell numbers in kidneys and lungs, and decreases levels of anti-nuclear antibodies (ANA) in lupus-prone mice. 22 In this study, we have evaluated the immunotherapeutic role of tolDCs generated by the HO-1 inductor cobalt (III) protoporphyrin IX (CoPP) in combination with two known tolerogenic drugs: dexamethasone (Dexa) and rosiglitazone (Rgz) in autoimmune mice. Given the background summarized above, tolDCs loaded with nuclear antigens, such as histones, arise as a promising self-antigen-specific therapy for SLE.…”
Section: Introductionmentioning
confidence: 99%